Deficiency of C-reactive protein or human C-reactive protein transgenic treatment aggravates influenza A infection in mice - Zhang, Zhuohan; Gao, Yongjun; Li, Li; Luo, Junhao; Gao, Rongbao (Frontiers in Immunology, 2022)
Abstract C-reactive protein (CRP) has been shown to be a potential candidate target in the immunotherapy of severe influenza A infection. However, it is unclear on the pathogenesis associated with CRP in influenza infections. Here, we used influenza A H1N1 CA04 to infect human CRP transgenic mice (KI), CRP knockout mice (KO), and wild-type mice (WT), respectively, and compared the viral pathogenicity and associated immune response in those mice. The results showed that CA04 infection resulted in 100%, 80%, and 60% death in KO, KI, and WT mice, respectively. Compared to WT mice, CA04 infection resulted in higher TCID50 in lungs on day 3 after infection but lowered HI antibody titers in sera of survivors on day 21 after infection in KI mice. ELISA assay showed that IFN- concentration was significantly increased in sera of WT, KI, or KO mice on day 7 after infection, and IL-17 was remarkably increased in sera of WT mice but decreased in sera of KI mice while no significant change in sera of KO mice on day 3 or 7 after infection. Quantitative RT-PCR showed that the relative expression levels of immune checkpoint CTLA-4, LAIR-1, GITR, BTLA, TIM-3, or PD-1 mRNA in the lung presented decreased levels on day 3 or 7 after infection in KI or KO mice. The correlation analysis showed that mRNA expression levels of the 6 molecules positively correlated with viral TICD50 in WT mice but negatively correlated with viral TCID50 in KI or KO mice. However, only LAIR-1 presented a significant correlation in each lung tissue of WT, KI, or KO mice with CA07 infection statistically. IHC results showed that LAIR-1 positive cells could be found in WT, KO, or KI mice lung tissues with CA04 infection, and the positive cells were mainly distributed in an inflammatory dense area. Our results suggested that deficiency of CRP or human CRP transgenic treatment aggravates influenza A virus infection in mice. CRP is a double sword in immune regulation of influenza infection in which IL-17 and immune checkpoint may be involved.